Az Alföld mezőgazdasága a két világháború között - Tímár, Lajos (Tér és Társadalom, 1993)
The analysis of the era between the two world wars is essential not only for abstract historical reasons but also for the understanding of the development of Hungarian agriculture after 1945. The framework, the characteristic features of agriculture that arc still the basis of agrarian development today, were formed during these two decades. The main features of the agriculture of the Great Plain, directly and indirectly, derived from the disproportionate structure of field crops. Thus the exaggerated rate of crop growing, in the case of fodder plants, the low level of hay, the one-sided cereal fodder production. The difficulties of the transportation obstructed the quick development of perishable commodities (fruits, vegetables). Of course the underdevelopment of the educational system also had its negatíve impact on the level of the agrarian production. In the growing on vegetables, in addition to the growing areas for onion and red pepper, several special growing regions were formed within the Great Plain. As a productive region, the area between the Danube and the Tisza became really important, where the growing of vegetables and fruit production developed considerably. The significant vegetable production of this region developed mainly due to social-economic, and partly to natural factors. The huge market of the capital was the most important key to development, but the possibilities of selling the products abroad were favourable in the second half of the 1930s for the whole agricultural sector. Among domestic prices, the rise of the prices of fruits and vegetables is apparent by 1938. Among the favourable natural geographical factors we have to emphasise, the fact that the sandy soils of the region, that quickly warm up to higher temperature, make the area especially suitable for growing early vegetables and fruits. An outstanding growing arca is that of Nagykőrös. In the case of almost all branches of animal breeding the livestock development in the Great Plain often shows an opposit tendency to Transdanubia, or its rate of growth is different. The difficulties of selling, that reached their climax in this period, had a less serious impact on the agriculture of Transdanubia due to its more favourable physical geographical situation for the various sectors, higher levei of development, and its closeness to the export markets. In fact, the quantitative growth in some sectors, owing to the above-mentioned circumstances, differed from that of the Great Plain so much that this led to significant qualitative intensity differences. The different rentability of the agriculture in these two areas enabled the technical development of the agriculture at different paces. It is strange and, at the same time, characteristic of the agriculture of the era, that the development of the vegetable growing and fruit culture, which was the most positive phenomenon, not only of the Great Plain, but also of the whole of Hungarian agriculture, is mainly linked to the scattered farms.